2022
DOI: 10.1097/pra.0000000000000637
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy in Intensive Case Management: A Multimethod Quantitative-Qualitative Study

Abstract: Cognitive-behavioral therapy (CBT) has been shown to improve clinical outcomes in schizophrenia and severe and persistent mental illness, but access to it remains limited. One potential way to improve access to CBT is to provide it through intensive case management (ICM) teams. A 90-week quality improvement study was designed to assess if CBT could be implemented in ICM teams. Self-selected ICM clinicians (N = 8) implemented CBT with their patients (N = 40). These clinicians attended weekly seminars (36 h tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…Only a few studies could be found in the recent literature to fit the criteria for this review. Consistent with recent systematic reviews and meta-analyses [25][26][27][28][29], our findings show that the RCTs selected for this review did not consider quality of life as a primary outcome. Contrary to a natural expectation that improving quality of life should be a significant outcome in any intervention, these studies focus mainly on clinical and cognitive improvement.…”
Section: Discussionsupporting
confidence: 87%
“…Only a few studies could be found in the recent literature to fit the criteria for this review. Consistent with recent systematic reviews and meta-analyses [25][26][27][28][29], our findings show that the RCTs selected for this review did not consider quality of life as a primary outcome. Contrary to a natural expectation that improving quality of life should be a significant outcome in any intervention, these studies focus mainly on clinical and cognitive improvement.…”
Section: Discussionsupporting
confidence: 87%